Lingkungan Pendidikan Islam Dalam Perspektif Al Qur’an - Waheeda bt Abdul Rahman (Sekolah Tinggi Agama Islam Nurul Iman Bogor, 2020)
Human caliph, has a big and important responsibility in protecting and preserving everything on this earth. To be able to create humans as caliphs or leaders who are fathonah, mandate, siddiq for tabligh, of course it requires knowledge and education, especially those based on the Qur'an and Hadiths, it must be applied from an early age.Feathered birds gather together. Birds with the same feathers will gather together. Shows how the importance of the environment affects a human being. Nature versus nurture is a fun thing that is often done by psychologists, educationists, sociologists and anyone with knowledge related to humans. Will a human being know more about his seeds or heredity, namely nature, or care, from the environment, education, family upbringing and government? The two terms above indicate the role that the environment affects on an individual's personality, especially the educational environment.The Islamic education environment in the perspective of the Qur'an can be a solution to form perfect human resources, which are beneficial to Islam and the nation. Like the adage,